Componentes do peso vivo, características da carcaça e da carne de cordeiros mestiços Hampshire Down terminados com dietas contendo silagens de grãos de milho - Andrade, Marília Belisário de (2007)
The live weight components, the physical-chemical characteristics, the mainly tissues proportions and the fatty acid profile of the Longissimus lumborum muscle of twenty four intact males lambs of Hampshire Down crossbreeding were analyzed. The lambs were distributed into three groups, each group feeding with different silages: 100% corn grain (control); 80% of corn grain with the addition of 20% sunflower seeds (sunflower) and 99% of corn grain with 1% urea (urea). In addition to silage the animals received 40% of concentrate. The treatments did not affect the live weight and the warm carcass weight at slaughter, as well as carcass yield, blood, skin, reproductive system with bladder, respiratory system, spleen, kidneys, perineal fat, liver, heart, empty gastrointestinal tract, head and feet. There was also no significant difference in the cold carcass weight, body condition, conformation of carcass, fat covering, fat consistency, meat color, thickness, loin area, crude protein, proportions of: muscle, bones, fat and other tissues of the Longissimus lumborum muscle. Cooking losses, myofibril fragmentation index and colors indexes L*, a* and b*, also did not differ by treatment. Those receiving the control treatment had a higher percentage of dry matter (26.05%) than those receiving urea treatment (25.38%) not differing from sunflower treatment (24.69%).The difference was not significant for the variables crude protein (20.48%), total lipids (1.53%) and cholesterol (67.09mg/100mg) of the Longissimus lumborum muscle. In the fatty acids profile, the control treatment had a higher percentage of palmitoleic acid (C16:In7) (1.51%), differing from sunflower treatment (1.11%) and both were not different from urea treatment (1.39%). There was a significant difference of the araquidic acid (C20:0) between urea treatment (0.15%) andcontrol treatment (0.08%), but were not different from sunflower treatment (0.12%). The others fatty acids, including the relation between the polyunsaturated fatty acids and the monounsaturated fatty acids (0.13%) and between n6 and n3 (7.10%) did not present significant differences. Lambs can be fattened with any tested diets: because there is no difference for weight, live weight components percentage, objective and subjective characteristics of carcass and physical-chemical characteristic of the Longissimus lumborum muscle and the proportion of muscle: fatty: bone.